Insecticidal activity of some essential oils against larvae of Spodoptera littoralis - Pavela, Roman (Fitoterapia, 2005)
Thirty-four essential oils were tested for insecticidal activity (fumigation or topical application) against larvae Spodoptera littoralis. Twenty essential oils applied by fumigation were highly toxic to the third instar of S. littoralis larvae. Two essential oils Nepeta cataria and Thuja occidentalis were highly toxic, with LC50< or =10.0 ml/m3. Five essential oils Salvia sclarea, Thymus mastichina, Origanum majorana, Pogostemon cablin and Mentha pulegium were toxic with LC50 between 10.1 and 20.0 l ml/m3. Twenty-three essential oils were highly toxic to the third instar of S. littoralis larvae after topical application. Eight essential oils Mentha citrata, N. cataria, S. sclarea, O. vulgare, O. compactum, Melissa officinalis, T. mastichina, and Lavandula angustifolia were highly toxic with LD50 < or =0.05 microl/larvae.
Keywords: Administration, Topical; zerav; Fumigation; Oils, Volatile; insekticidy; vykuřování; Spodoptera; Larva; Nepeta; Animals; aplikace lokální; šanta; Thuja; oleje prchavé; zvířata; Insecticides; larva